Conceptual Architecture for Agent-Based Modelling of Supplier Selection Conducted by a Supply Chain Dyad - Zair, Firdaous; Nejma, Maryam; Fourka, Mohamed; Cherkaoui, Abdelghani (International Journal of Supply Chain Management, 2019)
Within the fourth stage of industrialization, artificial intelligence and in particular the multi-agent systems paradigm is highly adopted. Within the agent approach, the industrial resources are defined as intelligent agents that negotiate with each other to implement dynamic reconfiguration and reach agility and higher customer satisfaction. In this paper a smart configuration of the agent-based system for multi-product dyadic supplier selection is proposed. The objective is to select suppliers for multiple products simultaneously in a vertical collaboration context while involving the customer of the purchasing company and considering its preferences. Negotiation experiments are conducted for initial validation of the proposed conceptual architecture.